Pelatihan Metode Penelitian Tindakan Kelas untuk Meningkatkan Kualitas Pembelajaran di SMPK Santa Clara Surabaya - Norbertus Tri Suswanto Saptadi (Journal of Sustainable Community Development (JSCD), 2021)
The task of the teacher is to improve the quality of learning in a systematic and controlled manner through the use of educational research. The results of interviews with the principal at SMPK Santa Clara Surabaya, have obtained information that most teachers have not been able to improve the quality of learning. Classroom Action Research (CAR) training is expected to be able to understand and apply educational research methods to help solve learning problems. The training methods include material explanation, assignment, proposal making, individual presentation, task discussion, presentation assessment and training evaluation. The results of the training evaluation conducted through the Google Form application showed that 7 participants (58.3%) stated it was sufficient, 3 participants (25%) said it was good, and 2 participants (16.7%) stated that it was very good in understanding and implementing classroom action research proposals based on training method used. The results of the assessment of the PTK proposal presentation showed a very good criterion value with details of the performance criteria of 5 people (41.6%), mastery of 3 participants (25%), quality of material 4 participants (33.3%), use of time 5 participants (41.6 %) and the ability to answer 4 participants (33.3%).